The Future of Digital Bureaucracy: Building an Organizational Culture for Sustainable SPBE - Karim, Jorry; A. Hatu, Rauf; Mustapa Wantu, Sastro; Abdussamad, Zuchri (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
Bureaucratic digitization through an Electronic-Based Government System is a strategic step in increasing the efficiency, transparency, and accountability of public services. This study aims to analyze the implementation in Gorontalo with a focus on organizational culture, human resource readiness, and the effectiveness of supporting policies. Using a qualitative approach, this study collected data through in-depth interviews, observations, and studies of relevant documents. The results of the study indicate that success depends not only on technological infrastructure, but also on the readiness of an adaptive organizational culture to change. A work culture that supports innovation and digitalization is an important factor in accelerating implementation. In addition, limited technological competence among State Civil Apparatus is still a major obstacle that needs to be overcome through continuous training and capacity building. In terms of policy, although related regulations are available, challenges in implementation at the regional level are still faced, especially in terms of coordination and understanding of policies. In conclusion, sustainability and effectiveness in Gorontalo require a holistic approach that includes strengthening organizational culture, improving apparatus skills, and more concrete policy synergy. With good collaboration between various stakeholders, bureaucratic digitization can run optimally in realizing more efficient governance that is responsive to community needs.